Pediatric metabolic outcome comparisons based on a spectrum of obesity and asthmatic symptoms. (3rd April 2019) - Perdue, Ashley D.; Cottrell, Lesley A.; Lilly, Christa L.; Gower, William A.; Ely, Brian A.; Foringer, Brad; Wright, Melvin L.; Neal, William A.
ABSTRACT: Rationale: Asthma and obesity are 2 of the most prevalent public health issues for children in the U.S. Trajectories of both have roughly paralleled one another over the past several decades causing many to explore their connection to one another and to other associated health issues such as diabetes and dyslipidemia. Earlier models have commonly designated obesity as the central hub of these associations; however, more recent models have argued connections between pediatric asthma and other obesity-related metabolic conditions regardless of children's obesity risk. Objectives: To examine the relationships between asthma, obesity, and abnormal metabolic indices. Methods: We conducted a cross-sectional study of 179 children ages 7 to 12 years recruited from a rural, Appalachian region. Our model controlled for children's smoke exposure, body mass index percentile, and gender to examine the association between children's asthma (based on pulmonary function tests, medical history, medications, and parent report of severity), lipids (fasting lipid profile), and measures of altered glucose metabolism (glycosylated hemoglobin and homeostatic model assessment 2-insulin resistance). Results: Our findings revealed a statistically significant model for low density lipids, high density lipids, log triglyceride, and homeostatic model assessment 2-insulin resistance; however, Asthma had a significant effect for the mean triglycerides. We also found an asthma–obesity interaction effect on children's glycosylated hemoglobin with asthmatic obese children revealing significantly higher glycosylated hemoglobin values than non-asthmatic obese children. Conclusions: Our findings support a connection between asthma and children's glycosylated hemoglobin values; however, this association remains entwined with obesity factors.